Political speech texts of the Indonesian Presidents in the reformation era - Megah S., Suswanto Ismadi (2022)
This study was aimed to explore ideological stances behind the political speech texts of the Indonesian presidents represented and evaluated by President Susilo Bambang Yudhoyono (SBY) and Joko Widodo (Jokowi) in the reformation era. The significance of this study was expected to contribute to the body of knowledge already established, both theoretically and practicality on Political Discourse Analysis, Critical Discourse, and Systemic Functional Linguistics. This study employs van Leeuwen's socio semiotic framework (2008) for the representation of social actors and Halliday and Matthiessen (2004) Transitivity analysis model incorporated and the attitudinal resources of the appraisal theory of Martin and White (2005) to uncover ideological stances in the ten presidential speech texts of SBY and Jokowi published officially by Indonesian government websites (Sekneg.go.id and setkab.go.id). This study basically adopts qualitative method, uses quantitative data analysis to assist the qualitative discussion to show the ideological inclination of SBY and Jokowi. The analysis looks at the grammatical roles and evaluation of important social actors involved in the political speech texts of SBY and Jokowi (e.g. president, government, people of Indonesia, politician, law enforcer and international people). The findings show that government was mostly represented and evaluated exceeded the five other social actors. This indicates that SBY’s ideological inclination came to the government to portrait himself by representing his government as the well- working government. SBY constructs to give positive image from the audiences to his well-organized in order to get support from the intended audiences to work together in developing the nation. It is similar to SBY, Jokowi also represents the government as the most favourable social actor exceed the five others to uphold the audiences’ trust that he is an acting taker to build his country via building infrastructures mostly around the nation. This study can be concluded that both presidents represented and the government as the most favorable social actor involved in their political speeches. This indicates that ideological stances disseminated to the audiences that they regard the government as the most important social actor to be prioritized in order SBY and Jokowi build positive image from their constituents. The last, I recommend for future researchers to study the comparison between Indonesian president and Malaysian prime minister of their political speeches through ‘SFL’ and Appraisal analysis to find the similarities and differences of their ideologies.